Contingencies of value : alternative perspectives for critical theory - Smith, Barbara Herrnstein (Harvard University Press, 1991)
Charges of abandoned standards issue from government offices; laments for the loss of the best that has been thought and said resound through university corridors. While revisionists are perplexed by questions of value, critical theory--haunted by the heresy of relativism--remains captive to classical formulas. Barbara Herrnstein Smith's book confronts the conceptual problems and sociopolitical conflicts at the heart of these issues and raises their discussion to a new level of sophistication.